DETERMINING TEACHING SCHEDULE AT STATE SENIOR HIGH SCHOOL 1 DEPOK USING ASSIGNMENT THEORY WITH HUNGARIAN METHOD AND NEW IMPROVED ONES ASSIGNMENT METHOD ASSISTED BY PYTHON - Hindarto, Catherine Richelle; Sanjaya, Febi (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
Every school has a lesson schedule that describes the allocation of teacher assignments to certain lesson hours in each class. The teaching schedule at State Senior High School 1 Depok is still made manually. Therefore, assignment theory using the Hungarian method and the New Improved Ones Assignment (NIOA) method assisted by Python is an alternative for automating the schedule creation process. The purpose of this research is to determine (1) the assignment model, (2) the application of the Hungarian method, (3) the application of the NIOA method, and (4) a comparison of the process and results using both methods from the teaching schedule at State Senior High School 1 Depok. The following research results were obtained. The assignment model can be arranged into assignment tables, which contain teacher codes in the rows, day and lesson hour codes in the columns, and the availability of teacher’s teaching hours, which is filled in with entry 1 if the teacher can teach and 0 if the teacher cannot teach in the corresponding cells. Those tables are processed using Python according to Hungarian and NIOA assignment algorithms. The difference in the application of the two methods is only in the algorithm for finding the initial basic feasible solution. Overall, the two methods applied produce the same schedule results. Differences in results are obtained if two teachers can only teach at the same time.